Genetic Diversity of Soil Microbes and its Ecological Significance - Hami, Hasan Jasim; AL-Gorani, Amal F.; Ajeel, Ahmed. K.; anisi, Ayam Al; Alrikaby, Nuha Jabbar (American Journal of Biology and Natural Sciences, 2025)
Microbes are the main performers of all activities related to the biosphere of the Earth. Alteration in microbial dynamics of the ecosystems by any means, including but not limited to climatic change affects the biogeochemical processes of terrestral ecosystems. Therefore, soil has the largest population of microorganisms since it offers hiding places; their contact with plant roots will guarantee their survival. Unfortunately most of the microbial populations in soil are not culturable and can only be characterized by the comparison of their metagenomic 16SrRNA and other housekeeping gene sequences with reference databases IconData: http://dx.doi.org/10.17504/atts.2016.084. Therefore, large-scale cultivation independent science is on the horizon since the number of uncharacterized soil microbes to classify is growing exponentially to the growth in sequence databases. Progressively, it is recognised that functional characterisation of the soil microbiome and especially of the interactions among its members requires full-scale genetic profiling of the entire soil microbial community, especially in the changing context of climate change. A profound comprehension of the variation in terrestrial soils by these detailed studies will unmask the role of the microbial community of the soil in the efficiency and organization of the other above-ground systems. We stressed on genetic identity of the soil and what is in stored for the soil bionetwork in relation to climate change in future.